Media Communications as a Context for Imprinting Formation - E. S. Radiontseva (Научный диалог, 2024)
The author of this article posits that media communications serve as a context for the formation of imprinting — a psychophysiological mechanism whereby impressions or images are etched into the brain, evolving into stable behavioral programs. The identification of these programs is facilitated through the analysis of media texts with a high attention coefficient. The study analyzed 200 media texts across various typological niches within the contemporary media system: online news outlets, social media platforms (VK, Odnoklassniki), and blogs, including the “Zen” platform. The findings indicate that different typological segments of the media system represent distinct behavioral programs. In online news outlets, behavioral programs are explicitly manifested in cognitive actions aimed at understanding processes related to Russia’s economic and political landscape. In social media, the prevailing behavioral program is encapsulated in a sentiment inspired by the phenomenology of serendipity. The “Zen” blog platform reveals imprinting through the categories of “irresponsibility,” “playfulness,” and “hooliganism.” In other blogs featuring high attention indices, imprinting is observed in the contemplation of professional issues related to activities in the digital space. The various typological niches of the media system are geared towards the formation of heterogeneous psychophysiological mechanisms, which transform into an axiological foundation that shapes diverse behavioral programs.